Osteosynthesis of the posterior pelvic segment with iliosacaral screws under 3D navigation control - Madeja, Roman; Jelen, Stanislav; Czerný, Daniel; Pleva, Leopold; Pleva, Leopold; Voves, Jiří; Demel, Jiří; Viskupič, Milan; Kopáček, Ivo (Úrazová chirurgie, 2021)
INTRODUCTION: For fractures of the posterior part of the pelvis and disjunction of the sacroiliac joint, iliosacral screws are used, which transfix the sacral process of the hip bone with the sacrum in the region of the S1 or S2 segment. The correct placement of these screws in the sacrum is important in order to avoid injury to the sacral nerve fibres or soft tissue injury ventrally and dorsally to the sacrum. 3D navigation provides the possibility of more precise control of drilling and screw insertion. It works on the basis of a 3D scan taken directly in the operating room using a C-arm with the possibility of 3D scanning. The aim of the work is to determine the operating times, the dose of intraoperative X-ray radiation and also the occurrence of postoperative complications during the introduction of iliosacral screws into the posterior segment of the pelvis under the control of 3D navigation. MATERIAL AND METHODS: In the years 2014–2020, we performed 13 osteosyntheses of the posterior segment of the pelvis using iliosacral screws under the control of 3D navigation at the Department of Surgery and Trauma and Emergency Surgery. We performed osteosynthesis using one or two cannulated screws with a diameter of 7.0 mm. The Ziehm Flat panel 3D fluoroscopy device and Vector Vision computer navigation were used during the surgery. For individual surgeries, we monitored the operating time in minutes, the dose of intraoperative X-ray radiation in cGY per cm2, as well as the time of intraoperative fluoroscopy in seconds. Postoperatively, we performed an X-ray check of the location of the iliosacral screws in four projections, in case of uncertainty, we clarified the position of the screws by CT examination. We monitored the incidence of postoperative complications within 90 days after surgery. One year after the surgery, we performed a control X-ray of the pelvis in four projections with the aim of detecting possible migration of osteosynthetic material or dislocation of the posterior segment of the pelvis after osteosynthesis. RESULTS: The group of 13 patients consisted of eight men and five women. All fractures were type C according to the AO-OTA classification. Eight patients (74 %) underwent osteosynthesis with one screw and five patients (26 %) with two screws. The median age of all patients in the cohort is 51 years (range: 33–73 years). The median weight of all patients in the cohort is 83 kg (range: 65–107 kg). The median intraoperative X-ray time of all patients is 1.14 min (range: 0.50–2.35 min). The median X-ray radiation dose is 853 cGy/cm2 (range: 591–1369 cGy/cm2). The median total operative time is 42 minutes (range: 28–62 min). CONCLUSION: Osteosynthesis of the posterior segment of the pelvis using 3D navigation is more accurate than fluoroscopic control of this surgical procedure and also 2D navigation because it allows drilling to be monitored in individual sections of the sacral bone. It is possible to assess the intraosseous position throughout the drilling of the channel for the iliosacral screw. In a small group of patients, we did not observe post-operative complications in the sense of injury to neurovascular structures and also malposition of screws.
Keywords: zobrazování trojrozměrné; Bone Screws; Imaging, Three-Dimensional; Treatment Outcome; vnitřní fixace fraktury; lidé; Fracture Fixation, Internal; výsledek terapie; Vector Vision; Surgery, Computer-Assisted; sakrokokcygeální krajina; sakroiliakální kloub; Humans; Sacrococcygeal Region; chirurgie s pomocí počítače; kostní šrouby; Sacroiliac Joint